The Kempalan Community of Jogja Family South Kalimantan (KEJOGJA Kal-Sel) in Maintaining Yogyakarta Gagrak Karawitan Gamelan Art in Banjarbaru City - Aulia Pratika; Melisa Prawitasari; Sriwati Sriwati (STKIP Taman Siswa Bima, 2025)
This research is motivated by concerns about the fading of Javanese cultural identity and nostalgia for their hometown, prompting them to strive to preserve their culture in a multicultural diaspora. The method used in this research is qualitative-descriptive. Data was collected through observation, interviews, and documentation. The research location is at the Pendopo Budaya Banjarbaru, which serves as the center for art and culture activities in Loktabat Utara Village, Banjarbaru North District, Banjarbaru City. The results show that the Kempalan Community of Jogja Family South Kalimantan (KEJOGJA Kal-Sel) successfully received a grant for a set of Yogyakarta gamelan from the DIY Palace as the main means of preserving karawitan art. The Bhinneka Tunggal Laras karawitan group, which is under the auspices of this association, is actively conducting rehearsals and performances, particularly involving the younger generation across ethnic groups. The values of Javanese culture such as guyub (harmony), grapyak semanah (friendliness), lembah manah (humility), unggah-ungguh (etiquette), ewuh pakewuh (mutual respect), srawung (gathering, interacting), and mutual cooperation are implemented in social interactions and ethics in these activities. It can be concluded from this study that the migrant community is able to preserve Javanese culture in a relevant and active way in a new environment. One way is by participating in cultural festivals and art exhibitions to preserve the culture while also introducing it to the wider community.